2003
DOI: 10.1002/chem.200390194
|View full text |Cite
|
Sign up to set email alerts
|

Organic Chemistry on Cold Molecular Films: Kinetic Stabilization of SN1 and SN2 Intermediates in the Reactions of Ethanol and 2‐Methylpropan‐2‐ol with Hydrogen Bromide

Abstract: We prepared thin molecular films of ethanol and 2-methylpropan-2-ol on Ru(001) substrates at temperature of 100 ± 150 K and examined their reactivity toward HBr. The reaction intermediates and products formed at the surfaces were unambiguously identified by the techniques of Cs reactive ion scattering (RIS) and low-energy sputtering. The reaction on the ethanol surface produced protonated ethanol, which is stabilized on the surface and does not proceed to further reactions. On the 2-methylpropan-2-ol surface, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 41 publications
2
25
0
Order By: Relevance
“…The Q values shown in Figure 3 are much smaller than the equilibrium constants of proton-transfer reactions in the aqueous phase: K eq = 6.0 10 10 for (CH 3 ) 2 NH, 4.3 10 10 for CH 3 NH 2 , and 1.7 10 9 for NH 3 at 298 K. [4] As shown in previous studies, [14,21] such a behavior arises because reactions at ice surfaces often stop at intermediate states along the reaction coordinate rather than proceeding all the way to the thermodynamically equilibrated states. In this respect, we define the apparent free energy for proton transfer at the ice surface according to the equation DG* ice = ÀRT lnQ, in analogy to the relationship between free energy and equilibrium constant.…”
Section: Discussionmentioning
confidence: 83%
“…The Q values shown in Figure 3 are much smaller than the equilibrium constants of proton-transfer reactions in the aqueous phase: K eq = 6.0 10 10 for (CH 3 ) 2 NH, 4.3 10 10 for CH 3 NH 2 , and 1.7 10 9 for NH 3 at 298 K. [4] As shown in previous studies, [14,21] such a behavior arises because reactions at ice surfaces often stop at intermediate states along the reaction coordinate rather than proceeding all the way to the thermodynamically equilibrated states. In this respect, we define the apparent free energy for proton transfer at the ice surface according to the equation DG* ice = ÀRT lnQ, in analogy to the relationship between free energy and equilibrium constant.…”
Section: Discussionmentioning
confidence: 83%
“…Studies in this line of research have greatly contributed to understanding of physics and chemistry of ice surfaces in the past decade. They include the RIS and LES studies of surface diffusion of water molecules, 28 ionization of electrolytes, [29][30][31] acid-base chemistry, 12,[32][33][34][35] proton transfer, [36][37][38][39][40][41] and various types of reactions that are either of fundamental interest [42][43][44] or related to environmental chemistry [25][26] and astrochemistry. 45,46 These subjects have been reviewed recently.…”
Section: Reactive Ion Scattering Of Lowmentioning
confidence: 99%
“…17,18,64 In particular, reaction intermediates can be trapped on a surface at a cryogenic temperature and be identified with RIS. [23][24][25][26][42][43][44] Quantitative measurement of surface adsorbates is an important goal in surface analysis. In the following, a relationship between the surface coverage of adsorbates and their RIS signal intensity is discussed.…”
mentioning
confidence: 99%
“…Recently, several research groups have investigated reactions occurring on the surface of ice or frozen molecular films at cryogenic temperatures. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] These studies demonstrated that a cold molecular surface can halt a reaction at an intermediate stage and that the reaction intermediate trapped on the surface can be identified with spectroscopic methods. [17][18][19][20][21] For example, Park et al [17] reported that the nucleophilic substitution (S N 1) reaction of tert-butyl alcohol with hydrogen bromide yields protonated alcohol and tertbutyl cation as metastable products on frozen alcohol films.…”
Section: Introductionmentioning
confidence: 99%